The Conditions of Freedom and their Metaphysical Implications for the Philosophies of Aristotle and Peirce - Acosta Lopez de Mesa, Juliana (Cognitio-Estudos: revista eletrônica de filosofia, 2012)
This article aims to present Peirce’s project as an organic system that is able to provide a reasonable account of our complex experience of freedom. For this reason, I will maintain that there are three conditions of possibility for human freedom that can be established according to an attentive reading of Aristotle’s works, namely, the contingency of the world, the existence of a being who can take advantage of the world’s contingency, and the capacity of a person to decide his or her own idea of happiness or final good in a human community. Even though Peirce did not think explicitly of these conditions, I will try to defend that they can be tracked, consolidated, and improved through Peirce’s philosophy. These conditions can be tracked, first of all, in their common perspective regarding the world’s element of contingency and openness to growth. Second, both philosophers think that human beings have the power to decide and actively participate in the world through experience and habit. Finally, both grant an important role to the community in their philosophies in order to give sense to persons’ actions.